NATO and its opponents. Mobilization and protest movements against the North Atlantic Alliance in Italy during the Cold War (1949-1989) - Andrea Guiso (Aracne, 2024)
During the Cold War, Italy was a stage for significant mobilization against NATO. The Atlantic Alliance, established to counter Soviet influence, encountered a complex environment in Italy, marked by a strong communist presence and pacifist movements. The protests were fueled by ideological opposition to American imperialism and concerns about national sovereignty and the risk of involvement in a nuclear conflict. Numerous demonstrations, strikes, and awareness campaigns characterized the activity of groups opposing NATO, involving left-wing political parties, trade unions, and civil society. This climate of contestation influenced the internal political debate and posed a constant challenge for Italian governments, forced to balance foreign policy needs with the pressures of domestic public opinion